An Efficient Method for Computing Resultant Systems. - Encarnación, Mark J. (Applicable algebra in engineering, communication and computing.)
A resultant system of a finite set of polynomials in two homogeneous variables is a finite set of polynomials in the coefficients of the original polynomials whose vanishing is a necessary and sufficient condition for the original polynomials to have a common non-trivial zero. We present an efficient general method for computing resultant systems. If there are s polynomials and each has degree at most d, the resultant system will have O(s2d) polynomials, each of which will have degree at most d2.